Cancrum Oris(Noma): An Early Sign of Acute Lymphoblastic Leukemia Relapse. (11th September 2019) - Madabhavi, Irappa; Modi, Mitul; Sarkar, Malay; K S, Sandeep; Shah, Mansi; Mallikarjuna, Vinay Sakaleshpura
Abstract: Cancrum oris is an infectious disease, which involves the orofacial tissues and adjacent neighboring structures in its fulminant course. Cancrum oris can occur rarely in chemotherapy-induced neutropenic patients with acute lymphoblastic leukemia. This rare case report reveals that cancrum oris can be a sign of acute lymphoblastic leukemia relapse. It is characterized by gangrenous lesions on skin with fine-needle aspiration cytology smear from the lesion showing infiltration of lymphoblasts. Cancrum oris can occur rarely in chemotherapy-induced neutropenic patients with acute lymphoblastic leukemia, but the presentation as an early sign of extramedullary disease relapse has not been documented in literature. Here we report a case of cancrum oris in a 27-year-old woman who presented with redness and swelling of the upper lip and infranasal area. She had a known case of acute lymphoblastic leukemia diagnosed 6 months back and was on regular multiagent chemotherapy for the same. Clinical examination revealed gangrenous lesions on infranasal, intranasal, and area involving the upper lip. Complete blood count, bone marrow aspiration, and cytology did not show any lymphoblasts. Blood culture and swab culture from the gangrenous area were sterile. Patient did not get better even after 7 days of broad-spectrum antibiotic treatment. With a high degree of clinical suspicion of isolated extramedullary relapse, fine-needle aspiration cytology from marginal and gangrenous area was taken and revealed infiltration of soft tissues by lymphoblasts. After receiving four cycles of multiple chemotherapy drugs, the skin lesions resolved. Treatment of cancrum oris involves the correction of the underlying immune status, antibiotics, and surgical reconstruction. The rare possibility of relapse of acute lymphoblastic leukemia presenting as cancrum oris should be kept in mind in patients with acute lymphoblastic leukemia on chemotherapy with skin manifestations.